THE INTERPLAY BETWEEN DAILY POSITIVE EVENTS AND DAILY STRESS SEVERITY ON INFLAMMATION IN ADULTHOOD. (16th November 2018) - Lee, S; Jun, H; Joo, S; Chai, H; Sin, N; Almeida, D
Abstract: In examining the dynamics between positive and negative experiences on health, previous studies suggest two possible pathways – the buffering hypothesis and blunting hypothesis. Buffering hypothesis suggests that positive experiences offset the harmful effects of negative experiences, while blunting hypothesis predicts that negative experiences will nullify the benefits of positive experiences. To test these hypotheses, this study examined interactions between daily positive events and daily stress severity on inflammation and whether the associations differ by age. Sample used were adults aged 34 to 82 (N = 597) from the Midlife in the United States Study Wave 2. Reports of respondents' daily experiences of positive events and stress severity were used as predictors, and log-transformed interleukin-6 (IL-6) and C-reactive protein (CRP) were used as outcome variables. Results showed significant interaction between daily stress severity and daily positive events, with evidence supporting the blunting hypothesis. Specifically, daily positive events were associated with lower levels of IL-6 (b = -0.16, p < .01) and CRP (b = -0.27, p < .01) among adults with lower levels of stress severity, but not for those with high stress severity. Buffering hypothesis was not supported; that is, daily positive events did not attenuate the associations between daily stress severity and IL-6 or CRP. Age did not moderate the interaction between daily positive events and stress severity on inflammation. Findings suggest that with severely stressful experiences, the benefits of positive events on inflammation diminishes significantly among midlife and older adults.